Safety and Effectiveness of High-Precision Hyperthermic Intraperitoneal Perfusion Chemotherapy in Peritoneal Carcinomatosis: A Real-World Study - Ba, Mingchen; Cui, Shuzhong; Long, Hui; Gong, Yuanfeng; Wu, Yinbing; Lin, Kunpeng; Tu, Yinuo; Zhang, Bohuo; Wu, Wanbo (Frontiers in Oncology, 2021)
Background Hyperthermic intraperitoneal chemotherapy (HIPEC) has been reported to effectively control peritoneal carcinomatosis (PC) in various patient populations, but there is a lack of real-world data. This study aimed to examine the safety and effectiveness of HIPEC in patients with PC in a real-world setting. Methods This was a retrospective study of patients with PC treated with the high-precision BR-TRG-I type HIPEC device between December 2006 and December 2016. Vital signs during HIPEC and adverse events were recorded. Effectiveness was evaluated by total objective remission rate (ORR), which was based on ascites’ remission 4 weeks after HIPEC. Results A total of 1,200 patients were included. There were 518 males and 682 females, with a mean age of 58.6 ± 6.5 years (range, 32–76 years). Among the patients, 93.6% of the patients (1123/1200) successfully received the three sessions of HIPEC, 158 had massive ascites. The changes of vital signs during HIPEC were within acceptable ranges, and patients only had a transient fever and abdominal distension. Regarding the HIPEC-related complications, hemorrhage was observed in seven (0.6%) patients, anastomotic leakage in four (0.5%), and intestinal obstruction in eight (0.7%). Nine (0.8%, 9/1200) patients had CTCAE grade IV bone marrow suppression, and three (0.3%, 3/1200) patients had severe renal failure (SRF), which were considered to be drug-related. The ORR of malignant ascites was 95.6% (151/158). Conclusion This real-world study strongly suggests that HIPEC was safe in treating PC patients with a low rate of adverse events and leads to benefits in PC patients with massive malignant ascites.